THE ROLE OF THE SUBDISTRICT GOVERNMENT IN THE IMPLEMENTATION OF THE FOSTER PARENT PROGRAM FOR STUNTING REDUCTION - Pit Anugerah Arruan Pasilong; Agus Sholahuddin; Sukardi (International Journal of Business, Law and Political Science, 2026)
Objective: This study aims to analyze the role of the Mook Manaar Bulat Sub-District Government in implementing the Foster Parent Program for stunting reduction in West Kutai Regency, East Kalimantan, and to identify the supporting and inhibiting factors affecting its implementation. Method: This study employed a descriptive qualitative case study approach. Data were collected through interviews, observations, and document analysis involving sub-district officials, village governments, health workers, community leaders, integrated health post cadres, foster parents, and beneficiary families. Data were analyzed using George C. Edward III’s policy implementation framework, covering communication, resources, disposition, and bureaucratic structure, with source triangulation to ensure data credibility. Results: The findings show that the sub-district government plays a strategic role as a coordinator, facilitator, supervisor, mentor, and mobilizer of community participation. Cross-sector collaboration among village governments, health centers, integrated health post cadres, Family Welfare Empowerment groups, community leaders, and foster parents has strengthened program implementation. However, limited funding, fragmented data, geographical barriers, transportation constraints, inconsistent reporting, and low public awareness remain major challenges. Novelty: This study proposes a collaborative local governance perspective by highlighting the sub-district government as the key intermediary connecting government institutions, communities, and private stakeholders. The findings demonstrate that strengthening sub-district governance and cross-sector collaboration can improve the effectiveness and sustainability of stunting reduction programs in rural and geographically disadvantaged areas.